The internal socio-economic polarization of urban neighborhoods, the case of Marseille - Argyro Gripsiou; Christophe Bergouignan (Investigaciones Geográficas)
The socio-economic inequalities of the different metropolitan neighborhoods have been carefully documented and analyzed in the social science literature. Starting from this premise, this article focuses on the less common neighborhoods in which two extremes coexist: very low-income households and high-income households. The objective is to identify the neighborhoods with a high internal socio-economic polarization, geolocate them in the urban space, characterize their population and housing stock, and measure their recent evolutionary trends. The empirical analysis focuses on the neighborhoods of Marseille (France), a city characterized by strong socio-spatial segregation between poor neighborhoods in the north and rich neighborhoods on the southern coast, and the presence of neighborhoods in which populations coexist with unequal resources. This empirical study is based on the fiscal and social data (Filosofi file) that allow knowing the income distribution and based on the census data to characterize the socio-demography and the type of housing of the population. In order to identify neighborhoods with intense internal socio-economic polarization and measure their evolution of income distribution, original poverty and wealth indexes have been developed, which synthesize the two extremes of this distribution. These neighborhoods with a high internal socio-economic polarization usually present certain distinctive aspects, such as their geographical location or a more or less rapid and intense gentrification process. However, some of them seem to escape this process, as evidenced by the contrasting trends in the recent evolution of income distribution and structural heterogeneity of the housing stock, in which small apartments and old buildings are very overrepresented.